Castiglione a Milano (Quaderni di Gargnano, 2021)
The essay aims to deepen the relation between Baldassarre Castiglione and the city of Milan. The first paragraph deals with the period of study spent in the capital of the duchy, where the author of the Cortegiano, still a teenager, and guest of his uncle senator, was able to learn about the profession and the language of diplomacy and to meet important figures of the humanistic and artistic culture of the city, who will appear in the pages of the Dialogue. Based on some passages from his correspondence, the second paragraph recounts Baldassarre's travels to Milan on the occasion of various military and diplomatic missions. The third paragraph highlights the specific references to the city found in his letters. The last section provides a textual and linguistic perspective, examining the famous letter to Iacomo Boschetto of 8 October 1499, written on the occasion of the entry of the King of France to Milan. It is a precious description of a parade from which a layered lexicon emerges, with names of weapons, clothes, and styles, which shows the richness of the language and of the courtesan letters, a first Italian sectorial dictionary. Il saggio vuole approfondire il rapporto tra Baldassarre Castiglione e Milano: un primo paragrafo tratta del periodo di studio trascorso nella capitale del ducato, dove l’autore del Cortegiano ancora adolescente, ospite dello zio senatore, ebbe modo di conoscere la professione e la lingua della diplomazia e di incontrare personaggi di rilievo della cultura umanistica e artistica della città, che compariranno nelle pagine del Dialogo. Il secondo paragrafo racconta attraverso alcuni brani dell’epistolario i viaggi di Baldassarre a Milano, in occasione di diverse missioni militari e diplomatiche; mentre il terzo riporta i riferimenti alla città reperibili nelle sue lettere. Infine, una prospettiva testuale e linguistica: viene presa in esame la celebre lettera a Iacomo Boschetto dell’8 ottobre 1499, scritta in occasione dell’entrate del re di Francia a Milano. Si tratta di una preziosa descrizione di una parata da cui emerge un lessico stratificato, con nomi di armi, vesti e fogge, che mostra la ricchezza della lingua e della epistolografia cortigiana, un primo vocabolario settoriale italiano.
Keywords: Baldassarre Castiglione; Il Cortegiano; Storia di Milano; Rinascimento; Milano nel Rinascimento; Storia della lingua italiana del Quattrocento e del Cinquecento; Lessicografia storica; Lingua ed Epistolografia cortigiana